Mechanical and structural properties of leukocyte‐ and platelet‐rich fibrin membranes: An in vitro study on the impact of anticoagulant therapy. (14th May 2020) - Ockerman, Anna; Braem, Annabel; EzEldeen, Mostafa; Castro, Ana; Coucke, Birgit; Politis, Constantinus; Verhamme, Peter; Jacobs, Reinhilde; Quirynen, Marc
Abstract: Objective and background: Little is known about structural and mechanical properties of leukocyte‐ and platelet‐rich fibrin (L‐PRF) membranes and even less about the influence of antithrombotic drugs on L‐PRF. The aim of this in vitro study is therefore to investigate mechanical properties, fibrin structure and cell content of L‐PRF membranes and the impact of anticoagulant therapy on L‐PRF. Methods: Blood samples were obtained from 12 volunteers and supplemented with either no, 1.25 IU, 2.5 IU, 5 IU, or 10 IU enoxaparin. L‐PRF membranes were characterized with tensile testing, scanning electron microscopy, and measurement of platelets and leukocytes. Control and enoxaparin‐supplemented L‐PRF membranes were compared. Results: At 10 IU enoxaparin, no L‐PRF membranes could be generated, whereas the low doses of 1.25 and 2.5 IU had no influence on L‐PRF properties. The mechanical properties, fibrin networks, and number of platelets and leukocytes of 5 IU supplemented membranes were unlike the control membranes, but were not found to be significantly different because of limited sampling and inter‐ and intra‐variability. Conclusion: Low doses of the anticoagulant enoxaparin do not affect mechanical properties, fibrin network, nor cellular content of L‐PRF, whereas high doses impair L‐PRF generation.